2018
DOI: 10.30773/pi.2018.09.20
|View full text |Cite
|
Sign up to set email alerts
|

BDNF Methylation and Suicidal Ideation in Patients with Acute Coronary Syndrome

Abstract: ObjectivePatients with acute coronary syndrome (ACS) are at an increased risk of suicide. It is well known that epigenetic mechanisms may explain the pathophysiology of suicidal behavior including suicidal ideation (SI), but no study has explored these mechanisms in ACS populations. MethodsIn total, 969 patients were initially recruited within 2 weeks of the acute coronary event and, 711 patients were successfully followed up 1 year after ACS. SI was evaluated using the relevant items on the Montgomery-Åsberg … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 19 publications
1
7
0
Order By: Relevance
“…Our study further found that patients with high suicide risk had lower serum VGF than those at low risk, and that the risk of suicide was negatively correlated with the level of VGF. Consistent with our present study, previous studies demonstrated that the lower levels of neuropeptide Y in the prefrontal cortex and caudate nucleus of suicide victims [27], and Kang et al found that hypermethylation of brain-derived neurotrophic factor (BDNF) plays a role in the epigenetic susceptibility of patients with acute coronary syndrome who have a history of suicidal ideation [28]. Taken together, these studies suggest that the VGF as one critical neuropeptides is also closely related to suicide risk.…”
Section: Discussionsupporting
confidence: 92%
“…Our study further found that patients with high suicide risk had lower serum VGF than those at low risk, and that the risk of suicide was negatively correlated with the level of VGF. Consistent with our present study, previous studies demonstrated that the lower levels of neuropeptide Y in the prefrontal cortex and caudate nucleus of suicide victims [27], and Kang et al found that hypermethylation of brain-derived neurotrophic factor (BDNF) plays a role in the epigenetic susceptibility of patients with acute coronary syndrome who have a history of suicidal ideation [28]. Taken together, these studies suggest that the VGF as one critical neuropeptides is also closely related to suicide risk.…”
Section: Discussionsupporting
confidence: 92%
“…The most commonly studied gene system was BDNF ( N = 10, including two studies investigating the TrkB.T1 gene; Kang et al, 2018; Ropret, Kouter, Zupanc, & Videtic Paska, 2021; Roy, Shelton, & Dwivedi, 2017; Kim et al, 2015; Kim et al, 2014; Maussion et al, 2014; Kang et al, 2013; Keller et al, 2011; Keller et al, 2010; Ernst et al, 2009). Of the eight studies examining methylation specifically in the BDNF gene, six found BDNF hypermethylation to be implicated across a range of SITB outcomes, while one study of SI found no group differences (Roy, Wang, Palkovits, Faludi, & Dwivedi, 2017), and an SD study found hypomethylation (Ropret et al, 2021).…”
Section: Resultsmentioning
confidence: 99%
“…Previous studies on blood from elderly people and patients with psychiatric or other conditions who also showed suicidal behavior ( i.e. suicide ideation, suicide attempts) have reported increased BDNF methylation over the controls[ 21 - 25 ]. To the best of our knowledge, there are only two studies to date that have reported decreased BDNF methylation in blood of psychiatric patients compared to controls.…”
Section: Discussionmentioning
confidence: 99%